Analizamos un fragmento de la obra Edipo rey - Ramirez Peche, Tabita Salome (2020)
The fragment of the work Oedipus King reveals the moral and spiritual strength of woman, her defense of life and human values as opposed to war._x000D_ It shows that the laws of men to be fair must have a moral backing and that when this is not the case, they move away from the fundamental principles of man. It can be surmised that the courage shown by the character of Antigone in this tragedy presumes Sophocles' allegation in favor of woman and the revaluation of her in the ancient world